Pengaruh penyuluhan safety riding dengan media audio visual terhadap peningkatan perilaku berkendara - Dryo Saputro; Lina Handayani; Maya Kusuma Dewi (Universitas Ahmad Dahlan, 2019)
Indonesia is a country with a high level of traffic accidents. Traffic accidents in Indonesia according to the World Health Organization is the third largest killer under coronary heart disease and tuberculosis. Traffic accidents are caused by several factors including human factors, vehicle factors, road factors, environmental factors and weather factors. Teenagers are one of the biggest contributors to traffic accidents. Age 13-18 years is the early teens where they just felt an interest in trying to ride a motorcycle. Teenagers think that they are mature enough to drive vehicles on the road, with the knowledge of shallow driving causing accidents. Traffic safety is greatly influenced by driverâ€™s discipline. Â Driverâ€™s discipline can increase the level of traffic safety. The purpose of this study is to determine the effect of providing audiovisual safety riding counselling to the knowledge and attitude of driving. The research was a quasi-experimental with one-group pre-test post-test design. Respondent in this study was 70 Muhammadiyah 4 Yogyakarta high school students. The sample was gathered by purposive sampling technique. The instrument used was a questionnaire. The study began with a pre-test and then a video screening and conducted a post-test with the same questionnaire. The data analysis test was the parametric paired sample T-test, the non-parametric Wilcoxon test. The results of the non-parametric Wilcoxon test analysis obtained p-value of 0.000. The results showed that there was an influence of counselling with audiovisual safety riding methods on knowledge. The results of the paired sample T-test test analysis obtained 0.000 which shows the effect of providing audiovisual safety riding on attitudes. There is an effect of counselling using audiovisual safety riding methods on students' knowledge and driving attitudes.